Africa : A handbook (Lagos, Nigeria : Daily Times, 1973)
The purpose of this handbook is to provide a reliable source of factual, precise and accurate information on the African countries, including those under colonial rule
Includes illustrations.
ijb, 18/01/2019
Loans
Keywords: Black History; Africa